2022
DOI: 10.1371/journal.pone.0259838
|View full text |Cite
|
Sign up to set email alerts
|

A calming hug: Design and validation of a tactile aid to ease anxiety

Abstract: Anxiety disorders affect approximately one third of people during their lifetimes and are the ninth leading cause of global disability. Current treatments focus on therapy and pharmacological interventions. However, therapy is costly and pharmacological interventions often have undesirable side-effects. Healthy people also regularly suffer periods of anxiety. Therefore, a non-pharmacological, intuitive, home intervention would be complementary to other treatments and beneficial for non-clinical groups. Existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 85 publications
0
5
0
1
Order By: Relevance
“…There is relatively little research in the field of haptic, but the authors argue that haptic has a variety of physiological and emotional properties that make haptic tasks possible. In this study, it was demonstrated that haptic techniques can provide an enjoyable, effective, and widely available alternative for alleviating state anxiety [19]. For example, the popular "stress relievers" on the market: "pinch and squeeze", "vent ball", "stress relieving pen", etc.…”
Section: Ways To Relieve Anxietymentioning
confidence: 99%
“…There is relatively little research in the field of haptic, but the authors argue that haptic has a variety of physiological and emotional properties that make haptic tasks possible. In this study, it was demonstrated that haptic techniques can provide an enjoyable, effective, and widely available alternative for alleviating state anxiety [19]. For example, the popular "stress relievers" on the market: "pinch and squeeze", "vent ball", "stress relieving pen", etc.…”
Section: Ways To Relieve Anxietymentioning
confidence: 99%
“…Researchers have investigated the potential of haptic devices for everyday use, and we anticipate their incorporation into our daily lives in the near future. Haptic devices using pneumatic actuators require air tanks or air blowers that constantly blow air as well as tubes to connect them [52][53][54]. Haptic devices that use high voltages typically receive power from power suppliers or voltage generators in laboratory environments [13,16].…”
Section: Wireless Design For Daily Usementioning
confidence: 99%
“…Post-operative pain increases because anxiety creates diminished tolerance and pain threshold, which -in turnprolongs the patient's post-operatory recovery in hospital or other care center. Touch and contact have been shown to reduce anxiety (24,25,(54)(55)(56)(57) through massage, or by holding their hands, besides being described as anxiolytic, and diminishes systolic blood pressure. (52) Antistress balls also help, which can be squeezed in case of perceived concern or anxiety.…”
Section: Nursing Care In the Trans-operativementioning
confidence: 99%